CHONDROID SKULL BASE TUMORS (A REVIEW OF LITERATURE) - T. G. Gasparyan; V. A. Cherekayev; A. Kh. Bekyashev (Опухоли головы и шеи)
Chondroid skull base tumors are a rare and little studied pathology; many problems of their classification, diagnosis and treatment remain to be solved. This group of neoplasms is referred to as bone tumors arising from the cartilaginous tissue of the skull base bones, particularly from the bones formed during chondral osteogenesis. The paper details the clinical picture, X-ray and morphological diagnosis of chondroid tumors. Particular attention is given to surgery and radiotherapy for this category of tumors.